PENGARUH PEMBELAJARAN COOPERATIVE TIPE QUESTION STUDENT HAVE TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS XI IPS SMAN 1 SUTERA KABUPATEN PESISIR SELATAN - Nelda, Yetri; Zafri, Zafri; Husnita, Liza (Pendidikan Sejarah, 2014)
Students ability low in giving example of history concept one of them is caused by history learning process still like giving information. There way to improve the understanding about giving example history concept through Cooperative Type Question Student Have learning. The purpuse of this research is to describe the influence Cooperative Type Question Student Have leraning to result of study studentsâs history grade XI IPS at SMAN 1 Sutera Kabupaten Pesisir Selatan. The advantages of this researchÂ are adding the knowledgeÂ and history teacher competenceÂ in using Cooperative Tipe Question Student Have learning method result study of history students.The kind of this research is quantitative research where the data is gotten through experiment at students grade XI IPS SMAN 1 Sutera Kabupaten Pesisir Selatan. The choosing sample in this research is taken based on the Randomized Control Group Only Design, then is gotten the experiment class is grade XI IPS 1 and control class is grade XI IPS 2. After do the research can be gotten that the result of study giving example of history concept class average in experiment class higher than control class is grade XI IPS 2. This thing can be seen from difference in posttest value of experiment class with 8,33 and posttest value of class control is 6,66 with hypothesis in tcount is 2,23 meanwhile ttable is 1,67. From the analysis of this research and discussion can be concluded that the applying Cooperative Type Question Student Have learning give influence in significance way to result study of student in giving example matery concept history subject grade XI IPS at SMAN 1 Sutera Kabupaten Pesisir Selatan. So that can be conclude that teacher can use Cooperative Type Question Student Have learning to giving example of concept.